Bank Runs, Bank Competition and Opacity - Toni Ahnert; David Martinez-Miera (ZBW - Leibniz Information Centre for Economics, 2021)
We model asset opacity and deposit rate choices of banks who imperfectly compete for uninsured deposits, are subject to runs, and face a threat of entry. Higher competition increases deposit rates and bank fragility, resulting in an intermediate socially optimal level of bank competition. We provide a novel theory of bank opacity. The cost of opacity is more partial runs by creditors, which induces costly liquidation of investment and lowers current profits. The benefit of opacity is to deter entry of competitors, which increases bank charter value. Banks can be excessively opaque, motivating transparency regulation.
Keywords: G01; G21; G28; 330; Competition; entry; opacity; fragility; bank run; global games; competition policy; transparency regulation